In plain sight - Box, C. J. (Box, C. J. Joe Pickett novel., 2016)
"Ranch owner and matriarch Opal Scarlett has vanished under suspicious circumstances during a bitter struggle between her sons for control of her million-dollar empire. Joe Pickett is convinced one of them have done her in, and when he becomes the victim of a series of wicked and increasingly violent pranks, Joe wonders if what's happening has less to do with Opal's disappearance than with the darkest chapters of his own past. Whoever is after him has a vicious debt to collect, and wants Joe to pay ... and pay dearly."--Page [4] cover.